MAKING APPLICATION FOR PROGRAM AND VRML OUTPUT DISPLAY USING HTML IN ONE V.50 - Andi Yogi Supardi; Irfan, SKom, MMSI Irfan, SKom, MMSI (Jurnal Sistem Informasi, 2002)
VRML (Virtual Reality Modeling Language) is one programming languagespecifically designed to create a 3 Dimensional object.The purpose of this paper is to make the My Editor, thus simplifying the writing oforders - orders in VRML, because it can avoid opening the windows (views) is morethan one window. And also can save time in the manufacture of 3 DimensionalObjects, and also saves the amount of memory used. Because to avoid calling thewindow in one view.In Making My Editor, the author uses HTML (Hyper Text Markup Language) andVB Script to create and design the My Editor.